Polygenic Threshold Model with Sex Dimorphism in Clubfoot Inheritance: The Carter Effect - Kruse, Lisa M. (Journal of Bone and Joint Surgery, Inc, 2008)
Background: Idiopathic clubfoot is approximately twice as common in males than in females. The reason for this discrepancy is unclear but may represent an inherent difference in the susceptibility to the deformity. If this difference is due to genetic factors it is predicted that in order to inherit clubfoot, females need to have a greater number of susceptibility genes than males. Females would also be more likely to transmit the disease to their children and have siblings with clubfoot. This phenomenon is known as the Carter effect, and the presence of such an effect supports a multifactorial threshold model of inheritance. Methods: Ninety-seven multiplex families with more than one individual with idiopathic clubfoot were studied. The study included 1093 individuals: 291 with clubfoot and 802 unaffected relatives. Rates of transmission by the thirty-seven affected fathers and twenty-six affected mothers were calculated, and the prevalence among siblings was determined in the nuclear families of affected persons. Results: Within these multiplex families, the prevalence of clubfoot was lowest in daughters of affected fathers (eight of twenty-four) and highest in sons of affected mothers (eleven of thirteen). Affected mothers transmitted clubfoot to 59% of their children (nineteen of thirty-two children), whereas affected fathers transmitted idiopathic clubfoot to 37% of their children (twenty-six of seventy children) (p = 0.04). Siblings of an affected female also had a significantly higher prevalence of clubfoot than siblings of an affected male (46% [fifty-four of 117] compared with 34% [sixty-seven of 197]; p = 0.03). Conclusions: This study demonstrates the presence of the Carter effect in idiopathic clubfoot. This effect can be explained by a polygenic inheritance of clubfoot, with females requiring a greater genetic load to be affected.